Morphology and General Reproductive Stages of Pangasius Nasutus From Sg. Pahang in Maran District, Pahang, Malaysia - Hassan, Mohd Zafri (2006)

(untitled)
The present study was conducted to describe the morphological differences between P. nasutus and P. conchophilus, to describe and classify the histology of oocyte and spermatogenic cells of mature P. nasutus and to observe the seasonal patterns of the gonadal stages in twenty specimens of P. nasutus and P. conchophilus from Maran. In order to signify the species differences, twenty specimens of Thai-origin P. conchophilus from a cage culture at Sungai Pahang near Pekan, Pahang, Malaysia were also examined. The morphometric measurements were presented in percentage of standard length (%SL), predorsal length (%PDL) and head length (%HL). Based on the classification results, all P. nasutus specimens were different from P. conchophilus in both populations, in terms of snout length, eye diameter, lower and upper jaw length. A total of 205 P. nasutus were caught during the study period, from October 2004 to September 2005 for the gonadal stages study of P. nasutus. Nine distinctive oocytes stages observed in the study were from oogonia to late vitellogenesis. Six microscopic oocytes developmental stages were assigned for the studied ovaries of P. nasutus, namely resting, maturing, mature, spawning, running and spent stages. Further, microscopic observation on the ‘whole-section’ of the testes revealed that four testicular development stages could be distinguished namely early spermatogenesis, spermatogenesis, maturation and spent stages. In this study, it was found that the female and male P. nasutus were reproductively active at the beginning of rainy season which commenced in the middle quarter of 2005, from March to September coincided with the South-West monsoon. The study also revealed that P. nasutus exhibits a single-modal spawning season in a year, with multiple release of eggs during a single period. Such condition showed that P. nasutus is a multiple-spawner as supported by the group-synchronous oocyte development of the ovary. However, spawning did not commence synchronously within the population with the obvious presence of various female and male reproductive stages within a single sampling month.